2010
DOI: 10.7150/ijms.7.55
|View full text |Cite
|
Sign up to set email alerts
|

Association between regulated upon activation, normal T cells expressed and secreted (RANTES) -28C/G polymorphism and asthma risk - A Meta-Analysis

Abstract: Regulated upon activation, normal T-cell expressed and secreted (RANTES) is one of the most extensively studied C-C chemokines in allergic inflammation. A growing body of evidence suggests that many cell types present in asthmatic airways have the capacity to generate RANTES, which directly supported the potential role of RANTES in asthma. A number of studies have evaluated the functional polymorphism -28C/G in the RANTES promoter region, which had been found to affect the transcription of the RANTES gene, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…They found that IL13 A2044G and RANTES G-28C were associated with an increased risk of athma in Asian populations. [20][21] We also observed that carriers of both A044G A/A and G-28C G/G had a more significant risk of developing asthma than those with either a single SNP, thus suggesting that synergism existed between the A2044G A/A and G-28C G/G genotypes.…”
Section: Discussionmentioning
confidence: 70%
“…They found that IL13 A2044G and RANTES G-28C were associated with an increased risk of athma in Asian populations. [20][21] We also observed that carriers of both A044G A/A and G-28C G/G had a more significant risk of developing asthma than those with either a single SNP, thus suggesting that synergism existed between the A2044G A/A and G-28C G/G genotypes.…”
Section: Discussionmentioning
confidence: 70%
“…Up to now, there were four meta-analysis investigations indicating controversial results about the correlation between these two polymorphisms and asthma. Three studies about the association of RANTES gene polymorphisms and asthma susceptibility reported that −28C/G polymorphism could increase the risk of asthma in Asian children or pediatric asthma in global population, while no relationship was found in −403G/A [35] , [36] , [37] . However, Zhang et al [38] observed contrary findings showing that −403G/A polymorphism would be a risk factor among atopic asthma patients, and no such association was indicated in −28C/G, which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter polymorphism of RANTES has shown to be related with atopic dermatitis [35]. Some reports have shown a relation between functional polymorphisms in the RANTES gene promoter and asthma [36,37].…”
Section: Discussionmentioning
confidence: 97%